2022
DOI: 10.1038/s41467-022-33200-4
|View full text |Cite
|
Sign up to set email alerts
|

CNS myelination requires VAMP2/3-mediated membrane expansion in oligodendrocytes

Abstract: Myelin is required for rapid nerve signaling and is emerging as a key driver of CNS plasticity and disease. How myelin is built and remodeled remains a fundamental question of neurobiology. Central to myelination is the ability of oligodendrocytes to add vast amounts of new cell membrane, expanding their surface areas by many thousand-fold. However, how oligodendrocytes add new membrane to build or remodel myelin is not fully understood. Here, we show that CNS myelin membrane addition requires exocytosis media… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 108 publications
1
19
0
Order By: Relevance
“…Blocking exocytosis with botulinum toxin B may reduce the delivery of proteins and lipids to the plasma membrane, therefore causing cell-autonomous effects on oligodendrocyte development in addition to blocking secretion. Both cell-autonomous and cell-non-autonomous mechanisms may be involved in the effect of blocking exocytosis on oligodendrocyte development ( Fekete et al, 2022 ; Lam et al, 2022 ). Our transwell rescue experiment and the comparisons between control cells in PD:ibot culture and control cells in control culture ( Figure 6 ) support the importance of secreted molecules but do not rule out cell-autonomous mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking exocytosis with botulinum toxin B may reduce the delivery of proteins and lipids to the plasma membrane, therefore causing cell-autonomous effects on oligodendrocyte development in addition to blocking secretion. Both cell-autonomous and cell-non-autonomous mechanisms may be involved in the effect of blocking exocytosis on oligodendrocyte development ( Fekete et al, 2022 ; Lam et al, 2022 ). Our transwell rescue experiment and the comparisons between control cells in PD:ibot culture and control cells in control culture ( Figure 6 ) support the importance of secreted molecules but do not rule out cell-autonomous mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent publications from the Zuchero and Nishiyama groups also utilized the ibot mice to investigate the role of VAMP2/3-mediated exocytosis in oligodendrocyte development and myelination ( Fekete et al, 2022 ; Lam et al, 2022 ). Together with data presented here, the three complementary studies utilized different Cre lines to express botulinum toxin-B in oligodendrocyte lineage cells ( NG2-Cre in Fekete et al, CNP-Cre in Lam et al, and PDGFRa-CreER in this study).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of MBP has been revealed to depend on the correct functioning of the SNARE machinery, which is not required for mRNA granule assembly and transport per se [ 128 ]. In a recently published paper by Lam et al, VAMP2/3-mediated membrane expansion in oligodendrocytes is indispensable for myelin formation due to the incorporation of axon-myelin adhesion proteins that are collectively required to form nodes of Ranvier [ 129 ].…”
Section: Discussionmentioning
confidence: 99%
“…OL lineage cells employ SNARE-mediated membrane fusion to enable secretion, vesicle, and membrane trafficking, as well as targeting and sorting of membrane proteins, which provide crucial functions at each of the different stages in OL development (Feldmann et al, 2011 ). Recently, we and others have shown that genetic expression of Vamp1, 2, and 3-specific B type botulinum toxin (BoNT/B), in OPCs using Cspg4-cre (Fekete et al, 2022 ) or Pdgfra-creERT (Pan et al, 2022 ) or in newly differentiated OLs using Cnp-cre (Lam et al, 2022 ) leads to severe hypomyelination due to inability of the Vamp2/3-cleaved OLs to produce myelin membranes. These findings suggest that a critical autocrine factor that is either secreted from newly generated OLs or is inserted into the plasma membrane of new OLs plays a critical role in myelination.…”
Section: Trafficking Of Cell Surface and Secreted Moleculesmentioning
confidence: 99%